Some Six-coordinated Rhodium(III) Compounds Derived from Semicarbazones of 4-Aminoantipyrne - Singh, Lakshman; Gupta, Pravin; Singh, Upma; Chakraborti, Indranil (Asian Journal of Chemistry, 2010)
Semicarbazones usually act as chelating agents with transition metal ions by bonding through the hydrazino-nitrogen and oxygen atoms. Current interest in the coordination chemistry of semicarbazones has arisen through their uses in biological systems. In the present work, we describe the synthesis of rhodium(III) complexes of ten semicarbazones derived from 4-aminoantipyrine and various aryl aldehydes. The complexes were characterized by elemental analyses, magnetic moments, IR and electronic spectral studies. The complexes were found to have the composition [Rh(Ligand)CI3]. All the complexes are diamagnetic and are sixcoordinated octahedral.